The IoT Challenges, Solution Framework And Implementation - Mittal, Pooja; Sharma, Monika; Nath Thulal, Amit (EAI Endorsed Transactions on Internet of Things, 2023)
The Internet of Things is a vast growing technology that is almost applicable in all fields and has simplified our lives. IOT is being used everywhere these days, including in smart cities, smart environments, security, smart business processes, smart agriculture, healthcare, and many more fields. Being able to cover various fields, is very challenging and presents various problems. This paper highlights IOT components, building blocks, enabling technologies, characteristics, applications, and products, as well as the issues encountered by them and lastly their causes. It brings forward seven steps of proposed solutions for handling and eliminating the problems encountered by almost all IOT devices and applications.  The main aim of this paper is to provide the solution for all the issues which have been talked about for years but could not be able to resolve.
Keywords: Internet of Things (IoT); Smart technologies; issues; enabling technologies; security; privacy; applications; implementation; proposed solution